Polymorphism in Melatonin Receptor 1A (MTRN1A) Gene in Chios, White Karaman and Awassi Sheep Breeds - Seker, Ibrahim; Ozmen, Ozge; Kul, Bengi Cinar; Ertugrul, Okan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
The aim of this study was to investigate polymorphism of the melatonin receptor 1A gene (MTNR1A) in Chios, White Karaman and Awassi sheep breed. A large fragment of the exon II of the MTNR1A gene was amplified and uniform fragment of 824 bp was obtained in 138 ewes (48 Chios, 40 White Karaman and 50 Awassi) of three breeds. The PCR products was digested with restriction endonuclease MnlI and RsaI, and genetic polymorphism was detected by PCR-RFLP. Biallelic polymorphism was found with restriction endonuclease MnlI and two genotypes were detected Mm (303bp, 236bp/67bp) and MM (236bp/67bp, 236bp/67bp). Allelic frequency for Chios, White Karaman and Awassi breeds was 0.90, 0.80 and 0.84 respectively for M allele; 0.10, 0.20 and 0.16 respectively for m allele, while genotypic frequency was 0.80, 0.60 and 0.68 for MM and 0.20, 0.40 and 0.32 for Mm respectively. No polymorphism at the RsaI cleavage sites was detected in three sheep breeds.
Sakız, Akkaraman ve İvesi Koyun Irklarında Melatonin Reseptör 1A (MTRN1A) Gen Polimorfizmi
Keywords: Turkish sheep breeds; Melatonin receptor 1A gene; Polymorphism